Advanced ovarian malignancy in pregnancy mimicking ovarian hyperstimulation syndrome: a case report - Kundur, Mythili; Rajanbabu, Anupama; Murali, Vinita; Keechilatt, Pavithran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Advanced ovarian malignancy is a rare occurrence in pregnancy. Here we report a case of primary infertility presenting in early pregnancy following invitro fertilization with features of Ovarian hyperstimulation syndrome unresponsive to treatment. Further evaluation revealed advanced ovarian malignancy. She was treated with chemotherapy followed by staging surgery at the time of elective cesarean at 35 weeks gestation. This case outlines the difficulties in diagnosis of ovarian cancer during pregnancy.